Indole-diterpenes alkaloid profiles of native grasses involved in tremorgenic syndromes in the Argentine Patagonia - Zabaleta, Gabriela; Lee, Stephen T.; Cook, Daniel; Aguilar, Marcelo Javier; Iannone, Leopoldo Javier; Robles, Carlos Alejandro; Martinez, Agustin (Elsevier, 2022)
One of the main intoxications to livestock in the Patagonia region of Argentina is the tremorgenic disease “Mal de Huecú", attributed to the consumption of the native grasses Poa huecu and/or Festuca argentina. In this report, five outbreaks of spontaneous intoxications were investigated. Several indole-diterpene alkaloids were identified in Poa huecu and Festuca argentina including the known tremorgen terpendole C and are likely the cause of “Mal de Huecú" disease.